A Randomised Controlled Trial of an Information Communication Technology Delivered Intervention for Children with Autism Spectrum Disorder Living in Regional Australia - Parsons, Dave; Cordier, Reinie; Lee, H.; Falkmer, Torbjorn; Vaz, Sharmila (Springer New York LLC, 2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. This exploratory randomised controlled trial tested the effectiveness of a tablet-based information communication technology early intervention application to augment existing therapy with the aim of improving visual motor, imitation, language and social skills in young children with ASD who reside in regional areas. Fifty-nine participants were recruited and randomised to either a therapy-as-usual group or intervention group. With the exception of the expressive language subscale on the Mullen Scales of Early Learning, no significant between-group differences were recorded for visual motor, imitation, receptive language and social skills of participants between baseline and post-intervention. When all participants were pooled and measured over time, improvements were shown in receptive and pragmatic language and social skills; these gains were maintained, thus suggesting skill acquisition.